When Grandma Gatewood Took a Hike - Houts, Michelle (Book collections on Project MUSE., 2016)
"It took her two tries, but in 1955, sixty-seven-year-old Emma 'Grandma' Gatewood became the first woman to solo hike the entire length of the Appalachian Trail in one through hike. Gatewood has become a legend for those who hike the trail, and in her home state of Ohio, where she helped found the Buckeye Trail"--Amazon.com.